2001
DOI: 10.1007/s001580100107
|View full text |Cite
|
Sign up to set email alerts
|

Robust optimization of an automobile rearview mirror for vibration reduction

Abstract: An automobile outside rearview mirror system has been analysed and designed to reduce vibration with a finite element model. Modal analysis is conducted for the calculation of natural frequencies. Harmonic analysis is utilized to estimate the displacements of the glass surface under dynamic loads. The model is verified with the vibration experiment for the parts and the assembled body. The structure of the mirror system is optimized for robustness defined by the Taguchi concept. At first, many potential design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…Chen et al [2] optimized the shape of a fuel tank, and Leiva et al [3] introduced size optimization to determine the location of weld points. Hwang et al [4] designed a rear-view mirror with enhanced dynamic performance by using shape optimization whose design parameters are determined by the Taguchi method. Kim et al [5] improved the fatigue life of a lower control arm by using the design of experiment approach.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [2] optimized the shape of a fuel tank, and Leiva et al [3] introduced size optimization to determine the location of weld points. Hwang et al [4] designed a rear-view mirror with enhanced dynamic performance by using shape optimization whose design parameters are determined by the Taguchi method. Kim et al [5] improved the fatigue life of a lower control arm by using the design of experiment approach.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with them, finite element analysis is more accurate than the multi-body system; however, it costs much more in terms of computer resources [1][2][3]. Model reduction techniques seek approximate solutions for the problem with many degrees of freedom within a subspace of small dimension.…”
Section: Introductionmentioning
confidence: 99%
“…This method of calculating the static ARIMA model was implemented using vibration signals from the database. It was found that for a variety of on-road signals a model of order [4,1,4] provided the best overall predictive performance while maintaining a satisfying computational efficiency.…”
Section: Arima -Predictive Model Of Vibrationmentioning
confidence: 99%
“…The recursive ARIMA algorithm adapts the prediction model in real time to the changes in the vibration pattern. In the algorithm applied, eight parameters of the ARIMA [4,1,4] model are estimated at every sample time.…”
Section: Recursive Arima Algorithmmentioning
confidence: 99%
See 1 more Smart Citation